Diagnóstico in vivo da sensibilidade de nematóides a diferentes antihelmínticos em ovinos do município de Alegre, Espírito Santo - Starling, Renan Zappavigna Costa (2015)
Wide variation in the degree of resistance to nematode populations is observed in chemical groups, including the anthelmintics, which is the main obstacle to obtaining control of worms in the sheep industry. The aim of the study was to evaluate the sensitivity of nematodes of crossbred sheep in semi-intensive farming in three properties to levamisole, albendazole, ivermectin, closantel and monepantel) used in worming. Fecal samples were analyzed at three different times (before, 7 and 14 days after treatment) using the technique Gordon and Whitlock (EPG) processed and calculated by the formulas Efficacy = (1- [OPGtreat / OPGcontrol] ) x100 and the formula Reduction OPG = 100 x [OPGt0 - OPGtn / OPGt0]. After the treatment groups differed significantly (p <0.05%) from before, however, animals treated with ivermectin in the after fourteenth days showed no significant difference when compared to the control group. In the fecal examinations the most common genera were Haemonchus and Trichostrongylus. In the first property, monepantel and albendazole showed the best EPG reduction results, the second property levamisole, closantel and monepantel showed significant results when compared to other drugs and in the third property the better EPG reduction results were levamisole and monepantel. In the properties A, B and C, resistant populations of nematodes to ivermectin were diagnosed. B and C on the properties, for nematode populations resistant to albendazole were diagnosed